Ψ‐v Computation of steady‐state conjugate heat transfer in backward‐facing step flow. Issue 6 (4th May 2021) - Dutta, Sailen; Kumar, Pankaj; Kalita, Jiten C.
Abstract: In this paper, we study steady‐state conjugate heat transfer over a backward‐facing step flow using a combination of a compact finite difference scheme for the ψ ‐ v form of the Navier–Stokes equations and a higher‐order compact scheme for the temperature equations on nonuniform grids. We investigate the effect of Reynolds number ( 200 ≤ R e ≤ 800 ), conductivity ratio ( 1 ≤ k ≤ 1000 ), Prandtl number ( 0.1 ≤ P r ≤ 15 ), and slab thickness ( h ≤ b ≤ 6 h ) on the heat transfer characteristics. Isotherms remain clustered near the reattachment point in the fluid, while the temperature in the solid decreases vertically, with the minima at the reattachment point. Heat transfer rate (HTR) increases with Re, the maximum at the reattachment point. The HTR increases with k till k = 100 after, which it becomes invariant as k → ∞ . Isotherms at the inlet become more disorderly with increasing Pr, and progressively clustered near the interface, indicating an increase in HTR, while the temperature in the solid region decreases with Pr . Increasing b decreases the HTR. In addition to obtaining an excellent match with results previously reported in the literature, we offer more comprehensive and previously unreported insights on flow physics.